Morphological adaptions of Quercus ilex leaves in the Castelporziano forest - Gratani, L; Marzi, P; Crescente, M F (Plant Ecology, 1992)
The annual course of vegetative growth of the most representative species of a Ouercus ilex L. forest in Castelporziano (Latium, Italy) was studied through periodical analysis of selected ecophysiological leaf indexes, for the period 1987-1990. The results demonstrate that the local climate facilitates continuous vegetative activity of the sclerophyllous species without a latent phase. The variable morphology of sun and shade leaves of (2- ilex illustrates the plant's response to environmental stress.
Keywords: Macro and microclimate; Morphological leaf analysis; Quercus ilex L.; Soil; Sun and shade leaves